Chronic Health Conditions and Substance Use Among Canadian Youth: A Nationally Representative Study: Problèmes de santé chroniques et usage de substances chez les jeunes Canadiens : étude représentative à l’échelle nationale - Mark A. Ferro; Alex Luther; Danielle Fearon; Joel A. Dubin; Laura Duncan; Scott T. Leatherdale; Dillon T. Browne; Ian Colman (The Canadian Journal of Psychiatry, 2026)
Background This study compared prevalence of youth substance use by gender and type of chronic health condition (CHC); estimated gender-stratified odds of substance use across CHCs; and, contrasted effect sizes across CHCs and genders. Methods Data come from 13,580 youth 12 to 17 years in the 2019 Canadian Health Survey on Children and Youth (48.7% girls). CHC was categorized as none (38.4%), physical only (39.8%), mental only (2.7%), neurodevelopmental only (6.7%), and multiple CHCs (MCHC; 12.4%). Multiple CHCs was defined as having ≥1 physical condition and ≥1 mental or neurodevelopmental condition. Youth self-reported alcohol, tobacco, e-cigarette, and cannabis use and gender identity (boy/girl; sparse data prevented inclusion of gender-diverse). Results Overall, 29.4% of youth used ≥1 substance. Girls were more likely to be occasional or regular consumers of alcohol (26.4% vs. 24.3%; P < 0.01), but boys were more likely to be frequent e-cigarette (7.2% vs. 5.2%; P < 0.01) and cannabis users (3.0% vs. 1.8%; P < 0.01). Prevalence was lowest for youth with no CHC or physical only and highest for youth with mental only or MCHC. Among girls, all CHCs were associated with increased odds of substance use (vs. no CHC; OR = 1.3 to 14.6; P < 0.05); whereas for boys, odds of substance use were increased among mental only, neurodevelopmental only, and MCHC (OR = 1.3 to 6.0; P < 0.05). Effect sizes for MCHC were typically significantly larger compared to physical only, but not when compared to mental or neurodevelopmental only. Effect sizes were also significantly larger for mental only compared to physical only. Associations between CHCs and substance use were typically larger for girls compared to boys. Conclusions Youth with CHCs, especially mental only, neurodevelopmental only, or MCHC are more likely to report substance use. Gender differences exist; magnitudes of association are larger for girls compared to boys.